Can Unemployed Youth Create Their Own Jobs? The Tunisia Business Plan Thesis Competition - Brodmann, Stefanie (World Bank, Washington, DC, 2012)
Tunisia, like the Middle East and North Africa (MENA) region in general, has long experienced unemployment, particularly among young university graduates. Unfortunately, job creation in existing enterprises is not sufficient to absorb a growing stream of graduates, and this tendency is unlikely to change in the short run. A recent Health District (HD) project is therefore trying to teach university graduates to create their own jobs. The business plan thesis competition uses the undergrad thesis writing process to teach students to create an enterprise project and write a business plan. Apart from professors, private sector coaches mentor the students. Completed theses are submitted to a competition, whose winners receive financial support and further coaching to incubate the enterprise. First results from the baseline survey and accompanying qualitative interviews show the passionate take-up of the program and warrant cautious optimism regarding the emergence of an entrepreneurial culture. The recent events in the MENA region, which first unleashed in Tunisia, have side action supported by the Tunisian employment Development Policy Lending (DPL).